La classe des débuts et ses épreuves : prolégomènes au processus de professionnalisation - Pierre Périer (Nantes Université, 2010)
This study analyzes the first moments and turning points experienced by secondary school trainee teachers while entering the process of professionalization, i.e., being in responsability before a classroom. The teaching contexts differ from the expected roles and situations. Thus, they lead to challenges as negociations, revisions and bereavements, that teachers try to cope with, more or less successfully. In our view, the diversity in the first steps of the teachers prefigures a process of individualization, where the subjectivities are requested, engaged and experienced more intensively. The emerging trajectories of professionalization are closely associated to the thinking on oneself, nevertheless, they remain a collective production. We investigate the teaching model suggested by this production.